PERAN SEKOLAH LUAR BIASA NEGERI MALINAU DALAM MENANGANI PESERTA DIDIK TUNAGRAHITA DI KABUPATEN MALINAU - SUKACA SUKACA (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
This research was conducted at the Malinau State Special School in Malinau Regency. This study aims to determine the role of the Malinau State Special School in dealing with mentally retarded students and to determine the school's collaboration with parents in dealing with mentally retarded students. Sampling in this study is by purposive technique. The number of samples is 10 people and the key informant is 1 person. The method used is a qualitative descriptive method with qualitative data analysis. The data filtering instruments used were observation, in-depth interviews and documentation. The results of the study can be concluded: the role of the Malinau State Special School in dealing with mentally retarded students is in providing basic lessons and recognizing and honing the skills abilities of students. Cooperation between the school and parents in dealing with mentally retarded students is in the form of exchanging ideas and information about the development of students. There are 4 obstacles experienced by mentally retarded students, namely difficulties in learning problems, adjustment problems, speech and language disorders, and personality problems. The solution in overcoming the obstacles of mentally retarded students can be in the form of providing appropriate learning services and creating the right learning environment. ABSTRAKPenelitian ini dilakukan di Sekolah Luar Biasa Negeri Malinau yang ada di Kabupaten Malinau. Penelitian ini bertujuan mengetahui peran Sekolah Luar Biasa Negeri Malinau dalam menangani peserta didik tunagrahita dan untuk mengetahui kerjasama sekolah dengan orang tua dalam menangani peserta didik tunagrahita. Pengambilan sampel dalam penelitian ini adalah dengan teknik Purposive. Jumlah sampel yaitu 10 orang dan key informan yaitu 1 orang. Metode yang digunakan adalah metode Deskriptif Kualitatif dengan analisa data Kualitatif. Instrumen penyaringan data yang digunakan adalah observasi, wawancara mendalam dan dokumentasi. Hasil penelitian dapat disimpulkan: peran Sekolah Luar Biasa Negeri Malinau dalam menangani peserta didik tunagrahita berupa memberikan pelajaran yang mendasar dan mengenali serta mengasah kemampuan keterampilan yang dimiliki peserta didik. Kerjasama antara pihak sekolah dengan orang tua dalam menangani peserta didik tunagrahita yaitu dalam bentuk bertukar pikiran dan informasi mengenai perkembangan peserta didik. Hambatan yang di alami peserta didik tunagrahita ada 4, yaitu kesulitan dalam masalah belajar, masalah penyesuaian diri, gangguan bicara dan bahasa, serta masalah kepribadian. Solusi dalam mengatasi hambatan peserta didik tunagrahita dapat berupa memberikan layanan pembelajaran yang sesuai serta menciptakan lingkungan belajar yang tepat.